BREAST LUMPS AND METHODS OF SELF EXAMINATION – A REVIEW - Thamilselvam P (Asian Journal of Medicine & Health Sciences, 2019)
Breast lump is a common issue and disease as females are concerned. It may present as painful lump or painless lump depending on its pathology. It is a very common finding around the world. The common breast lumps (Aberration normal development and involution of breast (ANDI), breast abscess, galactocele, fat necrosis of breast, breast cysts phyllodes tumour, fibroadenoma and cancer breast) occurring in women are reviewed in this paper about their clinical presentation and management. The understanding of benign breast disease and malignant breast disease is more important for the general practitioners who are having more exposures to common breast lesions. The knowledge about the malignant breast lesions especially in early stages when theses require radical and curative treatment, is more important on patient point of view as well. This chapter discusses about Breast Self-Examination (BSE) which would help family physician to educate the women for regular monthly examinations in different positions. Early detection of breast cancer is more important for curative treatment before this reaches advance stage when it will require palliative treatment. Patients presenting lumps in the breast are roughly from 40% to 70%. We are getting patients with breast lump in different route when they look for treatment. Some women notice their lump by breast self-examination. Few are identified through screening programs and some are diagnosed by surgeons. Sometime, most of breast lumps cases are diagnosed to be nonmalignant and these cases are to be in active follow up for further evaluation to rule out malignancy. Small lumps are sometime not detected by patients and doctors in heavy breasts of fatty females. In Malaysia, Carcinoma of breast is the most common malignancy in women.